PROSES COLLABORATIVE GOVERNANCE DALAM PEMBANGUNAN KAWASAN PERDESAAN DI KECAMATAN SOMAGEDE KABUPATEN BANYUMAS - Iin Piani (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2020)
Collaborative governance can be a solution for various public problems but in practice it is not easy to implement one of them is the implementation of collaborative governance in rural areas in Banyumas Regency. This study aims to determine the process of collaborative governance in rural area development in Banyumas Regency through a collaborative process of parties involved in coordinating rural area development carried out by several parties, namely the government, the community, and third parties. The study uses qualitative methods with a case study approach model. The results showed that face-to-face dialogue involved three parties, namely the rural area development coordination team, the community and a third party from academia namely Jenderal Soedirman University. Building trust is demonstrated by mutual support by participating in the coordination process in the form of meetings or meetings. Commitment to the process manifests in the dependence between the parties involved and cooperate with each other to achieve goals. The mutual understanding of the parties involved in the development of rural areas has made the three villages of Tanggeran, Klinting, and Kemawi become developed and independent villages by exploiting their potential. Preliminary results in the development of rural areas in Banyumas Regency were realized in the achievements of the collaborative process that resulted in a strategic plan consisting of activities and efforts to be carried out at the implementation stage of rural area development activities.